Comparative analysis of the representation of the water problem in the Kazakh mass media: case of Radio Azattyk and Azattyq-ruhy.kz (Herald of Journalism, 2026)
The article is devoted to the problem of covering water issues in the domestic media. The relevance of the research is determined by the need for a comparative analysis of media materials devoted to water issues, as well as the specifics of transmitting facts, choosing genre forms and presenting information to the audience. Thus, the issue of the development of industry journalism in the context of coverage of water issues is raised. At the same time, the main idea of the article was the different editorial position of the two media outlets and the scientific study of the transmission and interpretation of the same problem in different semantic tones.The purpose of the study is to determine the functional role of modern journalism as part of the crisis communication system and to identify the specifics of media construction of the image of the “water issue” in the Kazakh media (using the example of a comparative analysis of Radio Azattyk and azattyq-ruhy.kz).As part of the work, approaches to data submission were considered, the features of content policy were identified, and the works of foreign authors were studied. The researchers on the basis of which the research hypothesis is formed. The scientific novelty lies in the study of the water issue not just as an environmental topic, but as an object of crisis communication within the Kazakh media field. For the first time, a comparative analysis of the representation of transboundary water disputes in Kazakh-language resources with different edito-rial orientation is carried out, which makes it possible to identify the regional specifics of the formation of the information agenda in Central Asia.Additionally, the materials are classified according to the pitch (positive, negative and neutral). At the same time, the analysis includes not only traditional media, but also new media that play a significant role in the modern information ecosystem. The findings suggest the need to form an audience not only as a consumer of information, but also as its critical interpreter.
Keywords: water issues, Central Asia, Kazakhstan, media, ecology, ecoculture.